Biochemical Characterisation and In vitro Antitumour Effect of Parotoid Gland Secretions of the Egyptian Toad (Bufo relgularis) - Sabry Ali El-Naggar; Mohamed Aboulfotouh Basyony; Hany M. El-Wahsh; Seham Mohamed El-Feki; Ramadan Mahmoud Kandyel (Tropical Life Sciences Research, 2024)
This study aims to determine the biochemical compositions and the in vitro antitumour effect of the parotoid gland secretions (PGS) of the Egyptian toad (Bufo regularis). The total protein, lipid, carbohydrate contents, total antioxidant capacity (TAC), the median inhibitory concentration (IC50) of 2,2-diphenyl-1-picrylhydrazyl (DPPH), sodium dodecyl-sulfate polyacrylamide gel electrophoresis (SDS-PAGE) profile, amino acid analysis, gas chromatography–mass spectrometry (GC–MS) analysis and minerals were determined in PGS. The in vitro antitumour effect of PGS against human hepatocellular carcinoma (HepG-2), breast adenocarcinoma (MCF-7) and normal lung fibroblast (WI-38) cell lines were determined. The total protein, lipid and carbohydrate contents of PGS were 250 ± 15 mg/g D.W, 33 ± 3.2 mg/g D.W and 5 ± 0.65 mg/g D.W, respectively, while its TAC was 16.56 ± 0.12 mg/g D.W and the IC50 of DPPH was 51.95 ± 2.95 mg/mL. Six protein bands varied between 10 and 50 kDa were found in PGS. Among amino acid profile, arginine showed the highest content in PGS. GC-MS analysis showed that 11-octadecenoic acid methyl ester was the highest concentrations in PGS. The half-maximal inhibitory concentrations (IC50) of PGS against HepG-2, MCF-7 and WI-38 cells were 131.82 ± 6.14, 189.71 ± 8.95 and 685.65 ± 33.1 ?g/mL, respectively. In vitro study showed that treatment of HepG-2 and MCF-7 cells with PGS increased the percentages of early and late apoptotic. While the percentages of early and late apoptotic WI-38 cells after treatment with PGS were 2.1% and 3.7%. Cell cycle analysis showed that PGS treatment arrested HepG-2 and WI-38 in S-phase, while arrested MCF-7 cells in G2/M phase. The present study concluded that PGS has a potent antioxidant activity with in vitro antitumour effect against HepG-2 and MCF-7 cells.